Evolution of cranial capacity revisited: A view from the late Middle Pleistocene cranium from Xujiayao, China. Issue 163 (February 2022) - Wu, Xiu-Jie; Bae, Christopher J.; Friess, Martin; Xing, Song; Athreya, Sheela; Liu, Wu
Abstract: The Late Middle Pleistocene hominin fossils from the Xujiayao site in northern China have been closely studied in light of their morphological variability. However, all previous studies have focused on separated cranial fragments. Here, we report the first reconstruction of a fairly complete posterior cranium, Xujiayao 6 (XJY 6), confidently dated to ∼200–160 ka, which facilitated an assessment of its overall cranial size. XJY 6 was reconstructed from three of the original fragments—the PA1486 (No.7/XJY 6a) occipital bone, PA1490 (No.10/XJY 6b) right parietal bone, and PA1498 (No.17/XJY 15) left temporal bone—which originated from the same young adult individual. The XJY 6 endocranial capacity, estimated by measuring endocranial volume, was estimated using multiple regression formulae derived from ectocranial and endocranial measurements on select samples of Pleistocene hominins and recent modern humans. The results indicate that the larger pooled sample of both Pleistocene and recent modern humans was more robust for the endocranial capacity estimate. Based on the pooled sample using the ectocranial and endocranial measurements, we conservatively estimate the XJY 6 endocranial volume to be ∼1700 cm 3 with a 95% confidence interval of 1555–1781 cm 3 . This is close to Xuchang 1, which dates to 125–105 ka and whose endocranial volume is ∼1800 cm 3 . Thus, XJY 6 provides the earliest evidence of a brain size that falls in the upper range of Neanderthals and modern Homo sapiens . XJY 6, together with Xuchang 1, Homo floresiensis, Homo luzonensis, and Homo naledi, challenge the general pattern that brain size gradually increases over geological time. This study also finds that hominin brain size expansion occurred at different rates across time and space.